Systemic Bacterial Infection in a Captive Agouti (Dasyprocta leporina Linnaeus, 1758). (2nd March 2022) - Jones, Kegan Romelle; Lall, Kavita Ranjeeta; Suepaul, Rod; Garcia, Gary Wayne
Abstract : The agouti ( Dasyprocta leporina ) is a neotropical rodent which has the potential to be domesticated. As such, some research studies have been done on the biology of this animal. Recently, these animals are being kept in captivity as a source of animal protein. Animals which are kept in captivity may present diseases that would not have been reported in the wild due to lack of observation or the lack of occurrence. The aim of this short communication is to report a case of systemic bacterial infection that affected the lungs and liver of a captive agouti. Bacterial analysis revealed that the infection was caused by Escherichia coli . Bacterial infections have been reported in the mammary tissue as well as the skin of the agouti, but to the authors' knowledge, this is the first report of systemic infection in the agouti affecting several organs. This case was seen in a nine-month-old male agouti that was being housed at the University of the West Indies Field Station (UWI, UFS). The animal showed no apparent sign of disease except for lethargy and subsequently died before any treatment was administered. These findings showed that the agouti may have been under some stress (nutritional or environmental) which predisposed this animal to this infection. Future work has to address the nutritional requirements for the growing agouti as well as some treatment options for managements of similar cases in the future.